2009
DOI: 10.1130/b26271.1
|View full text |Cite
|
Sign up to set email alerts
|

Glacial geology and chronology of Bishop Creek and vicinity, eastern Sierra Nevada, California

Abstract: The valley of Bishop Creek, which drains part of the eastern fl ank of the Sierra Nevada, California, contains an unusually well-preserved set of middle to late Quaternary moraines. These deposits have been mapped by previous investigators, but they have not been quantitatively dated. We used the accumulation of cosmogenic 36 Cl to assign a chronology to the maximal glacial positions mapped in the valley. Our results indicate that the terminal moraines mapped by previous investigators as Tahoe were all deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
80
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 74 publications
(116 reference statements)
3
80
0
Order By: Relevance
“…Organic and 299 inorganic carbon input into Owens Lake also decreased abruptly between 26 and 20 ka 300 (Benson et al, 1996), and dessication events in the lake have been identified from 18.3 ka 301 onwards (Benson et al, 1996). The penultimate (Tahoe) glaciation was longer in duration and 302 more extreme, with moraines extending further down the catchments and their 36 Cl exposure 303 ages indicating retreat around 135 kyr ago (Phillips et al, 2009), in agreement with global 304 timings (e.g., Lisiecki & Raymo, 2009). Temperatures may also have been ~10 °C lower than 305 modern averages (Quade et al, 2003).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Organic and 299 inorganic carbon input into Owens Lake also decreased abruptly between 26 and 20 ka 300 (Benson et al, 1996), and dessication events in the lake have been identified from 18.3 ka 301 onwards (Benson et al, 1996). The penultimate (Tahoe) glaciation was longer in duration and 302 more extreme, with moraines extending further down the catchments and their 36 Cl exposure 303 ages indicating retreat around 135 kyr ago (Phillips et al, 2009), in agreement with global 304 timings (e.g., Lisiecki & Raymo, 2009). Temperatures may also have been ~10 °C lower than 305 modern averages (Quade et al, 2003).…”
mentioning
confidence: 98%
“…Exposure dating of LGM (Tioga) moraines shows that mountain 293 glaciers advanced to their peak extents at ~26 ka, and retreated rapidly at 21 to 17 ka along 294 the entire eastern margin of the Sierra Nevada (Phillips et al, 2009;Rood et al, 2011). In 295…”
mentioning
confidence: 99%
“…Subsequent work has demonstrated that the Recess Peak is in fact latest Pleistocene (Clark and Gillespie, 1997;Clark et al, 2003). Since the Hilgard lies outside of the Recess Peak, but within the zone where cosmogenic surface exposure ages have yielded ages close to the youngest Tioga moraines (Nishiizumi et al, 1989;Phillips et al, 2009), the Hilgard must represent a very late and minor Tioga deglacial oscillation. It is not now generally considered to be a separate glacial advance (Gillespie and Clark, 2011).…”
Section: Previous Studiesmentioning
confidence: 99%
“…The maps of the VTM survey are representative of the Hispanic period, and perhaps reach into the Holocene at 29 During the LIA, a period of slightly cooler, wetter climate prevailed in the temperate climates of the middle latitudes. In California, small cirque glaciers in the Sierra Nevada Mountains reached their maximum advance for the Holocene (Clark and Gillespie 1997;Phillips et al 2009;Bowerman and Clark 2011), and Mono and Silver Lakes in the Mojave Desert reached high stands (Enzel et al 1992). The climate has warmed since the early 19 th century, the termination of the LIA.…”
Section: Resultsmentioning
confidence: 99%